2019
DOI: 10.3390/en12030560
|View full text |Cite
|
Sign up to set email alerts
|

An Emissions Arbitrage Algorithm to Improve the Environmental Performance of Domestic PV-Battery Systems

Abstract: Domestic PV-battery systems are rarely operated in a way which specifically maximizes environmental benefit. Consequently the studies that seriously examine such systems often find that the greenhouse gas and pollutant emissions savings of rooftop PV, though still positive, are lessened by adding a domestic battery. This study shows thatby simulating a PV-battery system with a range of sizes that this need not be inevitable. A novel algorithm was designed specifically to perform 'emissions arbitrage': to charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The charger capacity is assumed to be 7 kW in this study, and the effect of varying the charger capacity from 3 kW to 22 kW is explored. Inverter and charge efficiencies are assumed as 97.0% and 98.5% respectively ( Sun et al., 2019 ). Battery self-discharge is disregarded in this study; we believe this is a reasonable simplification, as self-discharge rates for Li-ion batteries are generally low ( Zhang et al., 2020 ) and EVs are typically used shortly after charging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The charger capacity is assumed to be 7 kW in this study, and the effect of varying the charger capacity from 3 kW to 22 kW is explored. Inverter and charge efficiencies are assumed as 97.0% and 98.5% respectively ( Sun et al., 2019 ). Battery self-discharge is disregarded in this study; we believe this is a reasonable simplification, as self-discharge rates for Li-ion batteries are generally low ( Zhang et al., 2020 ) and EVs are typically used shortly after charging.…”
Section: Methodsmentioning
confidence: 99%
“…The lifecycle analysis (LCA) approaches used in these studies indicate that the origin of the electricity used for charging is key, with carbon intensity being a critical factor ( Petrauskienė et al., 2020 ; Raugei and Winfield, 2019 ; Rosenfeld et al., 2019 ; Wu et al., 2019 ; Burchart-Korol et al., 2020 ). In many studies, however, the carbon intensity of electricity is evaluated in a relatively simple manner that does not take full account of its increasingly important variation with time and location ( Rees et al., 2014 ; Sun et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers considered fitting a linear function for the hourly change in total CO 2 emissions (∆E) against the hourly change in total network demand (∆D), in order to obtain marginal emission intensity factors (MEF) as ∆E/∆D (McKenna et al 2017 ; Sun et al 2019 ). This method was originally proposed by Hawkes ( 2010 ) and has been modified by several researchers (McKenna et al 2017 ; Sun et al 2019 ; Siler-Evans et al 2012 ). Sun et al .…”
Section: Previous Workmentioning
confidence: 99%
“…Sun et al . ( 2019 ) employed this emission intensity modelling technique in conjunction with an emission arbitrage algorithm for studying the potential of PV-battery systems for emissions reduction. They concluded that the battery could fully repay its CO 2 costs of manufacturing if it were controlled to minimise operational emissions.…”
Section: Previous Workmentioning
confidence: 99%
“…This provides both national AEFs and regional AEFs, with the regional breakdown achieved using a power flow model. Sun et al [27] developed an emissions arbitrage algorithm to improve the environmental performance of domestic PV-battery systems. Focusing on Great Britain, this projected future timevarying MEFs out to 2050 and examined the environmental benefits of arbitraging on carbon emissions using a simple threshold-based charge-discharge strategy, i.e.…”
Section: Introductionmentioning
confidence: 99%